Feasibility for arteriovenous fistula creation with Ellipsys®. Issue 5 (September 2020) - Franco, Gilbert; Mallios, Alexandros; Bourquelot, Pierre; Hebibi, Hadia; Jennings, William; Boura, Benoit
Objective: To investigate the feasibility of percutaneous arteriovenous fistula creation in consecutive patients screened for first access creation. Methods: Prospective study of ultrasound mapping based on the following minimal anatomic requirements: a patent proximal radial artery and adjacent elbow perforating vein with straight trajectory, each greater than or equal to 2 mm in diameter and within 1.5 mm of each other. In addition, the same population was evaluated for feasibility of a distal radiocephalic fistula established. Results: One hundred consecutive patients were examined between November 2018 and January 2019. Sixty-seven were male (67%) and mean age was 61 years. Sixty-three patients (63%) and a total of 100 limbs (50%) were found to be eligible for a percutaneous fistula creation with Ellipsys ® . Thirty-seven percent of patients were ineligible because of the absence of both median cephalic and median cubital veins (15%), absence or inadequate elbow perforating vein and/or smaller than 2 mm proximal radial artery (14%), and/or distance greater than 1.5 mm (8%). We found suitable vessels for a surgical distal fistula creation in 91 extremities (45%), but this percentage dropped to 17% in patients over 70 years old. Among the 100 limbs eligible for percutaneous arteriovenous fistula, only 30 (30%) were eligible for radiocephalic arteriovenous fistula. Conclusion: More than 60% of patients were eligible for Ellipsys. The absence of veins at the elbow and a large distance between vessels were the most common limiting factors. Less than one half of the patients were candidates for surgical fistula and this percentage dropped significantly for older individuals.